Juventud y sexualidad : actitudes y conflictos entre "mozos" y "doncellas" en el marco social y familiar. Algunos ejemplos del siglo XVIII en el suroeste de Albacete. - Pilar Molina Gómez (Nuevo mundo - Mundos Nuevos, 2008)
This research try to approach a territory as problematic as prematrimonial young sexuality and the impediments that young people experiment to get married. All of this in a patriarchal and androcentrical system belonging to the Ancient Regime society in eigteenth century’s south Albacete. Across the Social History of the Family and gender analysis we will try to distinguish the different loving experiences and its links according to current rules – legal, moral or ecclesiastical-. In this way, we can not forget antique literature as an instrument to penetrate in the social and cultural context of the Early Modern Age society.